Peran Organisasi Non Pemerintah Human Initiative Sumatera Utara Terhadap Pemberdayaan Ekonomi Masyarakat Pesisir Kota Medan - Wati, Lina; Ardiansyah, Misnen; Pasrizal, Himyar (Jurnal Magister Ekonomi Syariah, 2022)
Success in development depends not only on a dynamic private sector and an efficient public sector but also on a robust civil society sector. The purpose of this research is to examine more deeply the role of the North Sumatra Human Initiative non-governmental organization for the economic empowerment of the coastal communities of Medan city, and to conduct a SWOT analysis (Strength, Weakness, Opportunity, Threat) regarding the potential for economic empowerment of the coastal communities of the Medan city, then to formulate a policy strategy. It is suitable to be applied to a community empowerment program in the final stage to recommend strategic opportunities or potentials to be developed for HI North Sumatra. The research approach uses descriptive qualitative with the SWOT analysis technique to analyze data. The research results were obtained in the last two years, the North Sumatra Human Initiative NGO was supported by PT. Pertamina has organized an economic empowerment program for the coastal communities of Medan City. In line with this, the vision and mission of the Medan City government are to prioritize economic empowerment for coastal communities. Therefore, the Medan City Government, the private sector, and NGOs are expected to be able to construct the economic development of the Medan City community to become more advanced and prosperous.